Seasonal variation in diel vertical migration of zooplankton and micronekton in the Andaman Sea observed by a moored ADCP. (January 2022) - Liu, Yanliang; Guo, Jingsong; Xue, Yuhuan; Sangmanee, Chalermrat; Wang, Huiwu; Zhao, Chang; Khokiattiwong, Somkiat; Yu, Weidong
Abstract: The diel vertical migration (DVM) behaviors of zooplankton and micronekton vary among species in response to diverse ambient conditions. Based on the observed mean volumes of backscattering strength (MVBS), we studied the mean features and seasonal variations of DVM in the Andaman Sea. Nocturnal-ascent DVM pattern prevailed throughout the observation period, with a mean downward (upward) migratory speed of 3.85 (3.81) cm/s. The DVM in this area exhibited a 3-layer vertical structure. Between the surface nighttime residence and the daytime residence below 300 m, there was a weak subsurface daytime residence probably formed by the assemblage of migrants avoiding aerobic predators. The variations in lower margin depth of surface nighttime residence and the upper margin depth of subsurface daytime residence were consistent with the variation in oxycline depth, which is closely related to thermocline variations. Compared with the premonsoon season, the MVBS was weaker, but the DVM was more active during the summer monsoon season, corresponding to the water clarity trend. Overall, equatorial Kelvin waves and monsoon winds presumably dominated the seasonal variations in DVM by modulating sea water properties such as oxygen concentration and transparency. Highlights: The diel MVBS difference revealed a 3-layer DVM structure in the OMZ area of the AS. Equatorial Kelvin wave modulated scattering layer depths by influencing the oxycline depth. Low MVBS and active DVM in summer monsoon season was associated with variation in water clarity.